SELF-REGULATED LEARNING DAN PERSEPSI DUKUNGAN SOSIAL DENGAN PRESTASI AKADEMIK MAHASISWA FAKULTAS USHULUDDIN IAIN IMAM BONJOL PADANG - Sudirman, Subhan Ajrin (Faculty of Ushuluddin and Humanities, 2015)
This research aimed to examine the correlations between self-regulated learning and social support perception with students academic achievement at Ushuluddin Faculty of State Institute for Islamic Studies Imam Bonjol Padang. This research used purposive sampling technique. The subjects of this research were 150 students. The data were collected by using, (1) The self-regulated learning scale, (2) The social support perception scale, and (3) documentation. The data were analyzed by using multiple regression of SPSS 13.0 for windows. The results of this research are: (1) There is very significant and positive correlation between self-regulated learning and students academic achievement (r = 0,325, p < 0,001 and R² = 0,106); (2) There is very significant and positive correlation between social support perception and students academic achievement (r = 0,284, p < 0,001 and R² = 0,081).